2012
DOI: 10.1111/j.1365-2966.2012.21298.x
|View full text |Cite
|
Sign up to set email alerts
|

Herschel imaging of 61 Vir: implications for the prevalence of debris in low-mass planetary systems

Abstract: This paper describes Herschel observations of the nearby (8.5 pc) G5V multi‐exoplanet host star 61 Vir at 70, 100, 160, 250, 350 and 500 m carried out as part of the DEBRIS survey. These observations reveal emission that is significantly extended out to a distance of >15 arcsec with a morphology that can be fitted by a nearly edge‐on (77° inclination) radially broad (from 30 au out to at least 100 au) debris disc of fractional luminosity 2.7 × 10−5, with two additional (presumably unrelated) sources nearby tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
147
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 93 publications
(190 reference statements)
14
147
1
Order By: Relevance
“…Hence, using these three stars as a sample, the outcome is one disk for one low mass planet system (1/1) and no disk for two high mass planet systems (0/2). Although this is small number statistics, we note that it is suggestive that the correlation between low-mass planets and debris disks recently found for G-stars by Wyatt et al (2012) also applies to M-stars. It is also intriguing that the only debris disk confidently detected in our current analysis surrounds the one star in the sample that hosts low-mass planets.…”
Section: Planets and Disk Relationship For The Gj 581 Systemmentioning
confidence: 93%
See 3 more Smart Citations
“…Hence, using these three stars as a sample, the outcome is one disk for one low mass planet system (1/1) and no disk for two high mass planet systems (0/2). Although this is small number statistics, we note that it is suggestive that the correlation between low-mass planets and debris disks recently found for G-stars by Wyatt et al (2012) also applies to M-stars. It is also intriguing that the only debris disk confidently detected in our current analysis surrounds the one star in the sample that hosts low-mass planets.…”
Section: Planets and Disk Relationship For The Gj 581 Systemmentioning
confidence: 93%
“…This is about three times the black body equilibrium temperature for the dust around this low luminosity M3-type star. Values of f T larger than unity have also been found for the debris disks around the G-type star 61 Vir (Wyatt et al 2012) and several A-type stars (Booth et al 2012). This is akin to disks resolved in scattered light which tend to be more extended than their sizes estimated from blackbody SED (Rodriguez & Zuckerman 2012).…”
Section: Dust Temperature In the Cold Diskmentioning
confidence: 96%
See 2 more Smart Citations
“…Bryden et al (2009) found no significant correlation between presence of RV planets (mainly giant planets) and debris disks. However, studies of hosts of lower-mass RV planets (less than the mass of Saturn) by Wyatt et al (2012) and hosts of Kepler planet candidates by Lawler & Gladman (2012) suggest that stars hosting lower-mass planets are more likely to also host debris disks. High-mass stars are intrinsically brighter than later-type stars, so a faint planet is much harder to directly detect around an A star than an M star.…”
Section: Introductionmentioning
confidence: 99%